An Economic Growth Model with Optimal Growth Rate and Individual Years of Schooling - Huan Yang; Donghan Cai; Zhongbin Chen (Discrete Dynamics in Nature and Society)
An economic growth model with individual years of schooling is present. It is proved that there exist optimal individual years of schooling for fixed wage growth rate. On the other hand, the economy has balance growth path for given individual years of schooling. Finally, we prove that there exist optimal individual years of schooling and economic growth rate such that the individual lifetime utility reaches maximum and the economy grows on a balance growth path.